Trends in Nepal’s Linguistic Demography: Insights from the 2021 Census - Sharma, Tilak Prasad; Sherpa, Dawa; Dhakal, Anju (Janajyoti Journal, 2025)
The linguistic landscape of Nepal is of mixed variety that has been developed due to various ethnic and cultural backgrounds. The research takes a look at the population pattern of the major language families and five major languages (Nepali, Maithili, Bhojpuri, Tharu, and Tamang) of Nepal between 1961to 2021 and the province-wise linguistic diversity to develop the language policy and cultural preservation approaches. The data used in analyzing the trends is from National Population and Housing Census (NPHC) of Nepal during 1961 to 2021 that covers information about the population sizes, the proportional representation of language families and the leading mother tongues. Indo-European family (with majority Nepali) grew up to 83.1 (24.2 million) in 2021, compared to 79.1 (7.4 million) in 1961, whereas Sino-Tibetan family experienced negative growth all the way down to 16.6 (down to 5 million in 2021) percent. The share of Nepali as the mother-tongue has decreased, as in 1981, 58.3 percent of Napili spoke it, compared to 44.9 percent in 2021; Tharu increased with 5.9 percent, and Maithili and Bhojpuri did not change significantly. There are 21 languages out of 124 that cover 95 percent of the population with the small ones facing the threat of extinction. The most prompted linguistic diversity (107 languages in each province) is found in Koshi and Bagmati, whereas Nepali is the common language owing in most of the regions with the sole exception (Madhesh). The linguistic environment of Nepal is showing signs of increasing variations as well as Indo-European paramountcy, which requires regional policies with a view to containing the unifying powers of the Nepali language without the need to eliminate the minor languages.